2014
DOI: 10.4103/2008-7802.157687
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional knowledge, practice, and dietary habits among school children and adolescents

Abstract: Background:Although nutritional status of children and adolescents is of great concern various interventions and modifications aiming at promotion of healthy eating behaviors have limited impact due to insufficient understanding of dietary habits between different age groups and genders. The aim of this study in not only evaluation of nutritional knowledge, practice, and dietary habits of primary school and junior high school students in Isfahan province, but also this research explore crucial differences rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 17 publications
(25 reference statements)
6
51
1
4
Order By: Relevance
“…Similar accounts were found in the literature on the lack of association between awareness and levels of physical activity, age, socioeconomic status, gender 16,25,28 and BMI, 28,30 except for the Italian study 27 which showed a slightly higher awareness score (1 point total score) in healthy subjects compared to overweight ones (p < 0.003). Studies are consistent on the grounds that food consciousness is related to environmental and family factors, besides state of motivation itself, and not to organic factors.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Similar accounts were found in the literature on the lack of association between awareness and levels of physical activity, age, socioeconomic status, gender 16,25,28 and BMI, 28,30 except for the Italian study 27 which showed a slightly higher awareness score (1 point total score) in healthy subjects compared to overweight ones (p < 0.003). Studies are consistent on the grounds that food consciousness is related to environmental and family factors, besides state of motivation itself, and not to organic factors.…”
Section: Discussionsupporting
confidence: 73%
“…14 The data reported in this analysis is useful for possible inferences about the population's eating habits, as poor awareness of food and nutrition refl ects on the consolidation of attitudes and food choices, even under interference from environmental factors hitherto mentioned. [16][17]25,27 As a diagnostic instrument, they support the planning of focused action plans, given ample evidence of the positive impact of educational interventions on FV intake. 25,[31][32] For this population, it is also important to combine the baseline awareness data to further investigation into motivational state (pre-contemplation, contemplation, decision, action) and environmental characteristics 17 of adolescents, so that the right strategies are established, including working with both parents and the community in which they live.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional knowledge of female pupils was higher than male in the study of Naeeni et al [26], Tallarini et al [27] and Asakura et al [28].…”
Section: Discussionmentioning
confidence: 76%
“…[12789] However, to encourage appropriate infant and young child feeding practices, apart from encouraging and supporting breastfeeding in both hospital and community settings, other steps such as promoting protection of working mothers and implementing standardized recommendations on the marketing of breast-milk substitutes can deliver beneficial results. [7]…”
mentioning
confidence: 99%